The dead girls' dance eaudiobook - Caine, Rachel (Morganville Vampires, 2009)
Claire Danvers has her share of challenges—like being a genius in a school that favors beauty over brains, dealing with the homicidal girls in her dorm, and above all, finding out that her college town is overrun with vampires. On the up side, she has a great roommate (who tends to disappear at sunup) and a new boyfriend named Shane, whose vampire-hunting dad has called in backup: cycle punks who like the idea of killing just about anything. Now a fraternity is throwing its annual Dead Girls' Dance and—surprise!—Claire and her equally outcast best friend, Eve, have been invited. When they find out why, all hell is going to break loose. Because this time both the living and the dead are coming out—and everybody's hungry for blood.